2008
DOI: 10.1103/physrevb.77.121202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of epitaxial strain on the ferromagnetic semiconductorEuO: First-principles calculations

Abstract: From first principles calculations we investigate the electronic structure and the magnetic properties of EuO under hydrostatic and epitaxial forces. There is a complex interdependence of the O 2p and Eu 4f and 5d bands on the magnetism in EuO, and decreasing lattice parameters is an ideal method to increase the Curie temperature, Tc. Compared to hydrostatic pressure, the out-of-plane compensation that is available to epitaxial films influences this increase in Tc, although it is minimized by the small value o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 26 publications
13
101
1
Order By: Relevance
“…21 Our experimental finding of a smooth enhancement of T C as a function of Gd concentration is in qualitative agreement with recent mean-field theoretical models. 28,29 Nevertheless, the magnetization curves deviate strongly from the Brillouin function upon doping, with the 7.7% composition showing the smallest deviation. Such deviations could indicate the presence of phase separation.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Our experimental finding of a smooth enhancement of T C as a function of Gd concentration is in qualitative agreement with recent mean-field theoretical models. 28,29 Nevertheless, the magnetization curves deviate strongly from the Brillouin function upon doping, with the 7.7% composition showing the smallest deviation. Such deviations could indicate the presence of phase separation.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Substituting Eu by Gd results in doping the material with extra electrons, and these electrons mediate via the double exchange mechanism an enhanced ferromagnetic coupling between neighboring 4f 7 ions. 4,5,28,29 Nevertheless, the small impurity potential present at each Gd site binds the extra electron so that a bound magnetic polaron 4 formed which becomes practically ferromagnetic at about 125 K. The diameter of these bound polarons could be of order three nearest-neighbors distances. For low doping, they are separated by regions without Gd doping.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…24,25 Following Ref. 26, the exchange constant J and the on-site orbital potential U for the Eu-4f orbitals are set, respectively, to J f = 0.77 eV and U f = 8.3 eV, while for the O-2p orbitals, we use J p = 1.2 eV and U p = 4.6 eV. Troullier-Martins norm-conversing relativistic pseudopotentials are used for Cu, Eu, and O.…”
Section: Methodsmentioning
confidence: 99%
“…The results agree rather well with previously published calculations. 26,32 In order to compare the band structures for two cells, we use the same k-space path. Standard high-symmetry points are specified for the primitive fcc BZ and also for the primitive tetragonal BZ (where applicable).…”
Section: Euo Electronic Structurementioning
confidence: 99%
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%